2006
DOI: 10.1080/08958370500305885
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of NT-ProBNP as an Early Cardiac Marker of Carbon Monoxide Poisoning

Abstract: Acute carbon monoxide (CO) poisoning may cause cardiotoxicity. The natriuretic peptides, including atrial natriuretic peptide, brain natriuretic peptide (BNP), N-BNP, and NT-proBNP (N-terminal pro brain natriuretic peptide), are endogenous cardiac hormones that may be secreted upon myocardial stress. The aim of this study was to assess the plasma NT-proBNP level in acute CO poisoning and to compare it with healthy control. After approval by the ethical committee, 15 healthy controls and 15 patients admitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…As the most common cause of death from poisoning worldwide, cardiovascular manifestations of acute CO poisoning have been the subject of various studies, but current evidence about the effects of chronic CO exposure on the cardiovascular system is limited (Ernst et al, 1998;Satran et al, 2005;Kalay et al, 2007; Davutoglu et al, 2006;Aslan et al, 2006). As chronic exposure to CO without acute toxicity is common in the environment and in some professions, unveiling this interaction is very important.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As the most common cause of death from poisoning worldwide, cardiovascular manifestations of acute CO poisoning have been the subject of various studies, but current evidence about the effects of chronic CO exposure on the cardiovascular system is limited (Ernst et al, 1998;Satran et al, 2005;Kalay et al, 2007; Davutoglu et al, 2006;Aslan et al, 2006). As chronic exposure to CO without acute toxicity is common in the environment and in some professions, unveiling this interaction is very important.…”
Section: Discussionmentioning
confidence: 98%
“…Cardiovascular manifestations of acute CO poisoning include myocardial dysfunction, ischemia, infarction, arrhythmias, and cardiac arrest, which have been the subject of various studies (Ernst et al, 1998;Satran et al, 2005;Kalay et al, 2007;Davutoglu et al, 2006;Aslan et al, 2006, Yildirim et al, 2005Wellenius et al, 2006). However, our knowledge about the effects of chronic CO exposure on cardiovascular system is limited.…”
mentioning
confidence: 98%
“…It is not always possible to identify this using the COHb level (2). Biochemical markers other than COHb are being studied to identify the clinical outcomes of this poisoning with neurotoxic and cardiotoxic effects in particular (3).…”
Section: Introductionmentioning
confidence: 99%
“…Acute CO poisoning includes brain, heart and kidneys (2,6). Acute coronary syndrome, myocardial damage, dysfunction, ischemia, infarction, fibrosis, atrial thrombus, arrhythmias, and cardiac arrest are the cardiovascular changes reported in acute CO poisoning (1,3,(6)(7)(8)(9)(10)(11)(12)(13). Previous reports with small number of patients with acute CO poisoning indicated that in some of the cases; attacks of atrial fibrillation (AF), premature beats, episodes of sinus tachycardia and alterations in ventricular repolarization were observed (14)(15).…”
Section: Introductionmentioning
confidence: 99%